G9a and HP1 Couple Histone and DNA Methylation to TNFα Transcription Silencing during Endotoxin Tolerance - Gazzar, Mohamed El (American Society for Biochemistry and Molecular Biology, 2008)
TNFα gene expression is silenced in the endotoxin tolerant phenotype that develops in blood leukocytes after the initial activation phase of severe systemic inflammation or sepsis. The silencing phase can be mimicked in vitro by LPS stimulation. We reported that the TNFα transcription is disrupted in endotoxin tolerant THP-1 human promonocyte due to changes in transcription factor binding and enrichment with histone H3 dimethylated on lysine 9 (H3K9). Here we show that the TNFα promoter is hypermethylated during endotoxin tolerance and that H3K9 methylation and DNA methylation interact to silence TNFα expression. Chromatin immunoprecipitation and RNA interference analysis demonstrated that, in tolerant cells, TNFα promoter is bound by the H3K9 histone methyltransferase G9a which dimethylates H3K9 and creates a platform for HP1 binding, leading to the recruitment of the DNA methyltransferase Dnmt3a/b and an increase in promoter CpG methylation. Knockdown of HP1 resulted in a decreased Dnmt3a/b binding, sustained G9a binding, and a modest increase in TNFα transcription, but had no effect on H3K9 dimethylation. In contrast, G9a knockdown-disrupted promoter silencing and restored TNFα transcription in tolerant cells. This correlated with a near loss of H3K9 dimethylation, a significant decrease in HP1 and Dnmt3a/b binding and promoter CpG methylation. Our results demonstrate a central role for G9a in this process and suggest that histone methylation and DNA methylation cooperatively interact via HP1 to silence TNFα expression during endotoxin tolerance and may have implication for proinflammatory gene silencing associated with severe systemic inflammation.